Use the factor theorem to prove that 2x+1 is a factor of f(x)=6x^2-5x^2-12x-4

in Algebra 2 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

2 Answers

The question is wrong. It should be f(x)=6x³-5x²-12x-4.

When 2x+1=0, x=-½.

2x+1 is a factor if f(-½)=0. Let’s see:


So 2x+1 is a factor.

by Top Rated User (796k points)

Assuming f(x)=6x^3-5x^2-12x-4

Using rational root test:

we know p/q: ±1/1,±1/2,±1/3,±1/6,±2/1,±2/2,±2/3,±2/6,±4/1,±4/2,±4/3,±4/6 are the test candidates.

Since we have to prove 2x+1 is a factor of f(x)

we check x=-1/2,

so f(-1/2) = 6x^3-5x^2-12x-4 = 6(-1/2)^3-5(-1/2)^2-12(-1/2)-4 =0

Since f(-1/2) =0

so, x - (-1/2) =  x + 1/2 = (2x +1)/2 is a root.

therefore, 2x+1 is a root of f(x)




by Level 6 User (19.5k points)

Related questions

1 answer
0 answers
asked Nov 16, 2011 in Algebra 2 Answers by anonymous | 265 views
Welcome to, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
85,653 questions
91,297 answers
108,838 users